1998
DOI: 10.1073/pnas.95.3.781
|View full text |Cite
|
Sign up to set email alerts
|

Event-related brain potentials in the study of visual selective attention

Abstract: Event-related brain potentials (ERPs) provide high-resolution measures of the time course of neuronal activity patterns associated with perceptual and cognitive processes. New techniques for ERP source analysis and comparisons with data from blood-f low neuroimaging studies enable improved localization of cortical activity during visual selective attention. ERP modulations during spatial attention point toward a mechanism of gain control over information f low in extrastriate visual cortical pathways, starting… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

120
979
7
13

Year Published

1999
1999
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 1,377 publications
(1,119 citation statements)
references
References 50 publications
120
979
7
13
Order By: Relevance
“…A method overcoming this limitations entails manipulating spatial selective attention. As mentioned above, early components of the VEP show a marked enhancement of amplitude when they were evoked by an attended stimulus as compared to when the identical stimulus was unattended (Mangun et al, 1993;Gomez-Gonzales et al, 1994;Mangun, 1995;Anllo-Vento and Hillyard, 1996;Hillyard and Anllo-Vento, 1998;Luck and Ford, 1998). This effect is linked to an ampli®cation of neural responses in those visual pathways related to the processing of the stimulus .…”
Section: Introductionmentioning
confidence: 91%
See 1 more Smart Citation
“…A method overcoming this limitations entails manipulating spatial selective attention. As mentioned above, early components of the VEP show a marked enhancement of amplitude when they were evoked by an attended stimulus as compared to when the identical stimulus was unattended (Mangun et al, 1993;Gomez-Gonzales et al, 1994;Mangun, 1995;Anllo-Vento and Hillyard, 1996;Hillyard and Anllo-Vento, 1998;Luck and Ford, 1998). This effect is linked to an ampli®cation of neural responses in those visual pathways related to the processing of the stimulus .…”
Section: Introductionmentioning
confidence: 91%
“…Therefore it was suggested that a selective attention mechanism focuses these resources to speci®c objects or locations in the visual ®eld without moving the eyes to that location (Hillyard et al, 1995;LaBerge, 1995;Hillyard and Anllo-Vento, 1998). Several metaphors have been used to explain this mechanism.…”
Section: Introductionmentioning
confidence: 99%
“…The Selection Negativity comprises a more negative response at the scalp when task-relevant features such as color, or spatial frequency are presented (Anllo-Vento and Hillyard, 1996;Hillyard and Anllo-Vento, 1998). Depth electrode recordings in macaque V4 have suggested that this structure contributes to the surface SN (Mehta et al, 2000).…”
Section: Relationship To Previous Event-related Potential (Erp) Studiesmentioning
confidence: 99%
“…Supporting this hypothesis, previous evidence indicates that modulation in attentional demand typically manifests as changes in GFP (Hillyard and Anllo-Vento, 1998;Luck et al, 2000). Moreover, converging data indicate that the 130 ms latency of the GFP modulation corresponds to a period when early attentional processes take place in inhibitory control tasks, subsequently to the very initial stage of the perceptual analyses of the stimuli (see Benikos et al, 2013;Roche et al, 2005;Thomas et al, 2009).…”
Section: Discussionmentioning
confidence: 86%